Integrating Social Media in Modern Radio Broadcasting - Davian Vlad (Social Sciences and Education Research Review, 2025)
Within the contemporary digital media landscape, radio broadcasters increasingly rely on social media platforms to distribute content, amplify audience engagement, and strengthen their brand identities. Therefore both commercial and public radio stations worldwide strategically integrate social media into their content distribution. Unlike traditional broadcasting, social media allows real-time interaction, extended content life cycles, and consistent audience data gathering. This paper focuses on the ways in which radio stations utilize social media platforms to enhance their content distribution and listener engagement in order to understand the ongoing digital transformation of radio broadcasting.